Strategi pengembangan karakter melalui internalisasi nilai-nilai pancasila pada anak usia dini di sekolah berbasis islam: studi multisitus di RTQ Firdaus, TK Madina Luhur, dan TK Muslimat NU 1 Tumpang - Se santi, Alma'idah Hayuning; Maulidya, Alifia Arif; Supriyanto, Achmad (2023)
This article examines the strategy of character development through the internalization of Pancasila values in early childhood education within three Islamic -based schools, namely RTQ Firdaus, TK Madina Luhur, and TK Muslimat NU 1 Tumpang. Character education is the primary focus in early childhood education, and Pancasila values are considered a fundamental philosophical foundation in Indonesia. This research elucidates how these three schools have successfully integrated Pancasila values into their curricula and school activities, including outings and social service initiatives. The internalization of Pancasila values is also reflected in their center programs. The research findings indicate that this strategy is effective in cultivating the character of young learners, fostering morality, social attitudes, and discipline. Th is article offers valuable insights into how Islamic-based schools can serve as agents in shaping character in alignment with Indonesia's national values, while also providing a foundation for strengthening character education at a broader level. Keywords: character development; pancasila; philosophical foundation of education